IMPROVING THE APPLICATION OF PROFESSIONAL SKEPTICISM IN AUDIT ENGAGEMENTS - I.Kuziev; F.Ochilov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
Professional skepticism is considered one of the fundamental principles ensuring the quality and reliability of audit engagements. In modern conditions, the rapid development of digital technologies, the increasing complexity of business processes, and the growth of financial fraud risks require auditors to strengthen professional skepticism during audit procedures. This study examines theoretical and practical issues related to improving the application of professional skepticism in audit engagements. The research analyzes international auditing standards, scientific approaches of local and foreign scholars, and current practices in audit organizations. The study identifies the major factors limiting the effective application of professional skepticism, including excessive reliance on management representations, lack of auditor experience, time pressure, and insufficient use of analytical procedures. Furthermore, the paper evaluates the role of professional skepticism in detecting material misstatements and fraud risks. The analysis section presents statistical indicators and comparative evaluations regarding audit quality and fraud detection effectiveness. Based on the findings, practical recommendations are developed to enhance professional skepticism through continuous professional education, integration of digital audit technologies, strengthening auditor independence, and implementation of risk-based audit approaches. The study concludes that improving professional skepticism significantly contributes to increasing audit quality, reliability of financial reporting, and stakeholder confidence in audit conclusions.